PENGARUH INFLASI, KEBIJAKAN DIVIDEN DAN PERTUMBUHAN PENJUALAN TERHADAP RETURN SAHAM - Rosyati, Tati (UNIVERSITAS DHARMAWANGSA, 2025)
This research aims to determine and obtain empirical evidence of the effect of inflation, dividend policy and sales growth on stock returns in consumer non- cyclical companies listed on the IDX in 2019-2023 and inflation data that occurred in 2019-2023 sourced from BPS. This type of research is quantitative research and uses secondary data in the form of audited annual financial reports sourced from the official website of the Indonesia Stock Exchange (IDX) and also uses inflation data based on the consumer price index sourced from the Central Bureau of Statistics. The population in this study is consumer non-cyclical companies listed on the IDX as many as 129 companies as the population, and the sample technique was taken using purposive sampling and meeting the criteria, 18 companies were sampled in 5 years of observation. The data analysis technique in this research uses panel data regression analysis in the eviews 9 software application. The results of this research simultaneously show that Inflation, Dividend Policy and Sales Growth have an effect on Stock Returns and partially show that inflation has no effect on stock returns, while dividend policy has an effect on stock returns, and also sales growth has no effect stock returns.